WhatsApp in Stroke Systems: Current Use and Regulatory Concerns - Calleja-Castillo, Juan M.; Gonzalez-Calderon, Gina (Frontiers in Neurology, 2018)
Smartphone use is extremely common. Applications such as WhatsApp have billions of users and physicians are no exception. Stroke Medicine is a field where instant communication among fairly large groups is essential. In developing countries, economic limitations preclude the possibility of acquiring proper communication platforms. Thus, WhatsApp has been used as an organizational tool, for sharing clinical data, and for real time guidance of clinical care decisions. It has evolved into a cheap, accessible tool for telemedicine. Nevertheless, regulatory and privacy issues must be addressed. Some countries have implemented legislation to address this issue, while others lag behind. In this article, we present an overview on the different roles WhatsApp has acquired as a clinical tool in stroke systems and the potential privacy concerns of its use.